IMPLEMENTASI METODE FONIK UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PESERTA DIDIK KELAS II SD NEGERI GUE GAJAH KABUPATEN ACEH BESAR - Anggito, Sulistio; Safiah, Intan; Hasniyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Low interest in reading among students is a common phenomenon. This occurs due to a lack of reading skills in students, especially in lower grades. One method to improve early reading skills is the phonics method. This study aims to examine the effectiveness of the phonics method and the activities of teachers and students when implementing the phonics method. This type of research is Classroom Action Research with a qualitative statistical approach using the Kemmis and McTaggart model (1998). The subjects of this study were second-grade students who have low early reading skills and the second-grade homeroom teacher of Gue Gajah Elementary School, Aceh Besar Regency as an observer. The data collection technique used observation sheets and performance tests. The data analysis technique in this study used a percentage formula for teacher and student activities, a classical percentage formula for performance tests and there was a classical success indicator of ≥75%. The results of the data analysis showed that there was an increase in teacher activity of 86.11% from the previous 47.22%, student activity of 90% from the previous 65% and classical early reading skills of 90% from the previous 63%. Thus, it can be concluded that the phonics method can improve the reading skills of class II students of SD Negeri Gue Gajah, Aceh Besar Regency.